Zero Car Growth A Challenge for Transport Justice - King, David (OECD Publishing, 2020)
This paper discusses the challenges to transport justice in the context of zero-car-growth policies. It analyses the car-dependence created by sprawling cities that necessitate access to automobiles if citizens want to fully participate in the economy, maintain social connections and achieve a desirable quality of life. It specifically highlights the complications this presents for cities in their efforts towards environmental, equity and economic goals largely achieved through reduced car use
Keywords: Transport